Analisis Pengaruh Maqashid Syariah Terhadap Fatwa DSN-MUI Tentang Penyelesaian Utang Murabahah - Hanif, Ahmad; Susanto, Hari; Armen, Rio Erismen (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This study aims to examine how the implementation of maqâshid syarî'ah in the DSN-MUI fatwas regarding the settlement of murabahah debts and to see how far the influence of maqâshid syar'ah on these fatwas. The method that the researcher uses in this research is a qualitative method and also a research on Islamic legal philosophy. The data collection method used is literature search. The data obtained were then processed and analyzed according to the research objectives. This study found that DSN-MUI implements and considers maqâshid syarîah in the fatwas regarding the settlement of murabahah debts. DSN-MUI does not mention maqâshid syarîah as a specific argument, but maqâshid is contained in the meaning of verses, hadiths, fiqh rules, choices of tarjih, and choices of other ijtihad mechanisms. Some of the maqâshid syarîah implemented by DSN-MUI in the fatwa regarding the settlement of murabahah debts include: hifzu al-mâl (guarding property) both from the side of producing it or from the side of maintaining it, sad bab al-nizâ' wa subul al-daghâ`in (closing the door disputes and hostilities), al-taysîr (facilitating) and dar`u al-darar (avoiding danger). The influence of maqâshid syarîah in the DSN-MUI fatwa can be observed based on the following: the selection of opinions (tarjih), looking for a better benefit even by leaving the opinion of the majority of scholars (jumhur), paying attention to the dynamics of the fatwa due to changes in 'illah, and presenting solutions and alternatives sharia-compliant contracts, paying attention to the consequences of a contract (ma'alat).